UKURAN PERUSAHAAN, UKURAN DEWAN DIREKSI, KEPEMILIKAN MANAGERIAL, KUALITAS AUDIT DAN PENGUNGKAPAN PENGENDALIAN INTERNAL - Daniel Satrio Partogian; Totok Dewayanto (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of firm size, board size, managerial ownership, and audit quality as independent variable toward internal control disclosure as dependent variable.This study uses secondary data obtained from the Indonesia stock exchange (idx). This research using a sample as many as 339 manufacturing companies registered in BEI year 2014 – 2016. The methods used in this research is purposive sampling method. Statistical techniques used in this study is a multiple regression.The results obtained from this research shows the firm size and managerial ownership has the significant positive influence on the internal control disclosure. But not board size and audit quality showed significant results against internal control and disclosure.